2005
DOI: 10.1073/pnas.0507979103
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of MKK6 in chondrocytes of transgenic mice inhibits proliferation and delays endochondral bone formation

Abstract: Accumulating in vitro evidence suggests that the p38 mitogenactivated protein kinase (MAPK) pathway is involved in endochondral ossification. To investigate the role of this pathway in endochondral ossification, we generated transgenic mice with expression in chondrocytes of a constitutively active mutant of MKK6, a MAPK kinase that specifically activates p38. These mice had a dwarf phenotype characterized by reduced chondrocyte proliferation, inhibition of hypertrophic chondrocyte differentiation, and a delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 48 publications
10
83
0
Order By: Relevance
“…Interestingly, mutant mice harboring the MTK1 kinase-inactive mutant allele, which is incompetent for p38 signaling, display abnormalities in axial skeletogenesis, although the role of MTK1 in terminal chondrocyte differentiation was not addressed (23). In addition, transgenic mice expressing a Col2a1 promoter/enhancerdriven, constitutively active MKK6 mutant have shorter limbs associated with delayed chondrocyte terminal differentiation and reduced Col10a1 expression (24), suggesting that excessive MKK6 signaling inhibits chondrocyte proliferation and subsequent differentiation. In contrast, enforced MKK6 activation of the p38 pathway in synovial fibroblasts induces terminal chondrocyte differentiation markers, including type X collagen, and mineralization (65).…”
Section: Gadd45␤ Regulation Of Genes Involved In Terminal Chondrocytementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mutant mice harboring the MTK1 kinase-inactive mutant allele, which is incompetent for p38 signaling, display abnormalities in axial skeletogenesis, although the role of MTK1 in terminal chondrocyte differentiation was not addressed (23). In addition, transgenic mice expressing a Col2a1 promoter/enhancerdriven, constitutively active MKK6 mutant have shorter limbs associated with delayed chondrocyte terminal differentiation and reduced Col10a1 expression (24), suggesting that excessive MKK6 signaling inhibits chondrocyte proliferation and subsequent differentiation. In contrast, enforced MKK6 activation of the p38 pathway in synovial fibroblasts induces terminal chondrocyte differentiation markers, including type X collagen, and mineralization (65).…”
Section: Gadd45␤ Regulation Of Genes Involved In Terminal Chondrocytementioning
confidence: 99%
“…Ablation of the MAPK kinase kinase (MAP3K), MEKK4/MTK1, causes skeletal patterning defects in the mouse embryo (23). Moreover, Col2a1 promoterdriven MKK6 transgene overexpression leads to decreased chondrocyte proliferation and delayed terminal differentiation to hypertrophy (24). Constitutive activation of the MAP2K, MEK1, responsible for ERK activation caused persistence of proliferating chondrocytes and delayed hypertrophic maturation (25), whereas in vitro studies using pharmacological inhibition showed that ERK activation is required for chondrocyte hypertrophy (26).…”
mentioning
confidence: 99%
“…For instance, p38 has been found to regulate the transcriptional activity of SOX9, the master transcription factor controlling chondrocyte differentiation. 18 Moreover, ATF2 is expressed in resting and proliferating chondrocytes during endochondral bone development. Atf2-deficient mice display a uniform dwarfism due to reduced chondrocyte proliferation, disorganized chondrocyte columns and impaired endochondral ossification.…”
Section: Overview Of the P38 Mapk Signaling Pathwaymentioning
confidence: 99%
“…Among these extra functions are control of cell metabolism and cellular differentiation (Pestell et al, 1999). To control and balance chondrocyte proliferation during limb bud development, cyclin D1 expression is reduced in the resting and proliferating chondrocytes of mice embryos, a phase in chondrogenesis where Sox9 is highly induced and where it plays a decisive role (Zhang et al, 2006). Moreover, Akiyama et al showed that in the growth plate of E16.5 Sox9 knock-in mutant mice (mice in which all chondrocytes overexpressed Sox9) the expression of cyclin D1 mRNA and protein was severely reduced (Akiyama et al, 2004).…”
Section: Sox9 In Undifferentiated Adult Rat Msc 2897mentioning
confidence: 99%